Now You See It, Now You Do Not: A Case of Infliximab-Induced Vanishing Bile Duct Syndrome. Issue 7 (July 2019) - Shah, Parth; Larson, Brent; Wishingrad, Marc; Nissen, Nicholas; Björnsson, Einar; Sundaram, Vinay
Abstract : ABSTRACT: Infliximab is a commonly used antitumor necrosis factor alpha agent, especially in patients with inflammatory bowel disease. It has been associated with drug-induced liver injury including immunologic reactions, with rare cases of acute liver failure. We describe a patient with chronic cholestasis and loss of intrahepatic bile ducts after therapy with infliximab for refractory ulcerative colitis consistent with a diagnosis of vanishing bile duct syndrome. About 3 months after the initial infusion, the patient developed subfulminant liver failure and required liver transplantation.